Make way for ducklings - McCloskey, Robert, 1914- (New York, The Viking press, 1941)
Mr. and Mrs. Mallard proudly return to their home in the Boston Public Garden with their eight offspring.
Illustrated lining-papers.
"First published August 1941."
Children's Catalog (Wilson)
Elementary School Library Collection (Bro-Dart)
Caldecott 1942 Medal Winner
3.1
Keywords: Ducks -- Fiction; Ducks -- Fiction; Caldecott 1942 Medal Winner/M; Boston (Mass.) -- Fiction